Compensation of the odd-even effects in araliphatic self-assembled monolayers by nonsymmetric attachment of the aromatic part - Dauselt, John; Zhao, Jianli; Kind, Martin; Binder, Robert; Bashir, Asif; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2011)
The integrity, chemical identity, packing density, and molecular orientation in SAMs formed by anthracene-substituted alkanethiols (Ant-n) with a variable number of methylene groups (n) in the aliphatic linker on Au(111) and Ag(111) substrates were studied by a combination of several complementary experimental techniques. The Ant-n molecules were found to form well-defined and highly ordered SAMs on these substrates, with very small inclination of the anthracene backbone. In addition, the Ant-n SAMs exhibited odd−even effects, that is, dependence of the molecular orientation and packing density on the length of the aliphatic linker, with the parity of n being the decisive parameter. While the direction (sign) of this odd−even behavior on gold and silver is the same as for SAMs of biphenyl- and terphenyl-substituted alkanethiolates and -alkaneselenolates, suggesting a common reason behind this phenomenon, the presence of a strong substrate−headgroup−C bending potential, the extent of the odd−even effects in the Ant-n films is noticeably smaller than in the latter systems. This behavior can be explained by the additional rotational degree of freedom of the anthracene unit in the case of the Ant-n SAMs due to its nonsymmetrical attachment to the adjacent alkyl linker. This permits the adoption of an almost upright orientation of the aromatic part regardless of the parity of n. The above behavior is an instructive example that even seemingly subtle changes of the molecular structure may have noticeable implications for the properties of the resulting assemblies.